Role of mitochondria during female gametophyte development and fertilization in A. thaliana - Martin, María Victoria (2014)
Plants alternate between two generations during their life cycle: the diploid sporophyte and the haploid male and female gametophytes, in which gametes are generated. In higher plants, the female gametophyte or embryo sac is a highly polarized seven-celled structure that develops within the sporophytic tissues of the ovule. It has been proposed that mitochondria are crucial in many cell signaling pathways controlling mitosis, cell specification, cell death and fertilization within the embryo sac. Here, we summarize recent findings that highlight the importance of this organelle during female gametophyte development and fertilization in plants.